The Relationship Between Job Demands and Social Well-Being Among Remote Workers in South Africa: The Moderating Role of Employee Resilience - Brown, Ameerah (School of Management Studies, 2023)
The present study aimed to investigate the relationship between job demands and social wellbeing, with employee resilience as a moderator. A quantitative research design was employed to explore the associations between the study variables. A total of 173 employees working remotely or hybrid completed the online questionnaire consisting of six measures (that is workload pressure, task interdependence, professional isolation, family-to-work conflict, social well-being and employee resilience). Participants included employees from various organisations based in South Africa. The Pearson correlation analysis demonstrated a negative relationship between workload pressure and social well-being. Unexpectedly, there was a positive relationship between task interdependence and social well-being. Results revealed no relationship between social well-being and two job demands (that is, professional isolation and family-to-work conflict). As proposed, the relationship between employee resilience and social well-being was significant and positive. The moderation analyses revealed that employee resilience did not moderate the relationship between job demands and social well-being. Given these findings, it may be necessary for South African organisations to implement employee resilience-building interventions. The findings, theoretical contributions, practical implications, study limitations and recommendations for future research are discussed with reference to appropriate literature.